Comparison of agreement between different measures of blood pressure in primary care and daytime ambulatory blood pressure. Issue 7358 (3rd August 2002) - Little, Paul; Barnett, Jane; Barnsley, Lucy; Marjoram, Jean; Fitzgerald-Barron, Alex; Mant, David
Abstract: Objective : To assess alternatives to measuring ambulatory pressure, whichbest predicts response to treatment and adverse outcome. Setting : Three general practices in England Design : Validation study Participants : Patients with newly diagnosed high or borderline high bloodpressure; patients receiving treatment for hypertension but with poor control. Main outcome measures : Overall agreement with ambulatory pressure; prediction of high ambulatory pressure (>135/85 mm Hg) and treatment thresholds. Results : Readings made by doctors were much higher than ambulatory systolic pressure (difference 18.9 mm Hg, 95% confidence interval 16.1 to 21.7), as were recentreadings made in the clinic outside research settings (19.9 mm Hg, 17.6 to 22.1). This applied equally to treated patients with poor control (doctor v ambulatory21.4 mm Hg, 17.3 to 25.4). Doctors' and recent clinic readings ranked systolic pressure poorly compared with ambulatory pressure and other measurements (doctor r =0.46; clinic 0.47; repeated readings by nurse 0.60; repeated self measurement 0.73; home readings 0.75) and were not specific at predicting high blood pressure(doctor 26%; recent clinic 15%; nurse 72%; patient in surgery 81%; home 60%), with poor likelihood ratios for a positive test (doctor 1.2; clinic 1.1; nurse 2.1, patient in surgery 4.7; home 2.2). Nor were doctor or recent clinic measures specific in predicting treatment thresholds. Conclusion : The "white coat" effect is important in diagnosing and assessing control of hypertension in primary care and is not a research artefact. If ambulatory or home measurements are not available, repeated measurements by the nurse or patient should result in considerably less unnecessary monitoring, initiation, or changing of treatment. It is time to stop using high blood pressure readings documented by general practitioners to make treatment decisions